2021
DOI: 10.3389/fpls.2021.610283
|View full text |Cite
|
Sign up to set email alerts
|

Secondary siRNAs in Plants: Biosynthesis, Various Functions, and Applications in Virology

Abstract: The major components of RNA silencing include both transitive and systemic small RNAs, which are technically called secondary sRNAs. Double-stranded RNAs trigger systemic silencing pathways to negatively regulate gene expression. The secondary siRNAs generated as a result of transitive silencing also play a substantial role in gene silencing especially in antiviral defense. In this review, we first describe the discovery and pathways of transitivity with emphasis on RNA-dependent RNA polymerases followed by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 263 publications
(298 reference statements)
0
40
0
Order By: Relevance
“…The mechanism of antiviral RNA silencing in plants reveals a related process, termed as post-transcriptional gene silencing (PTGS). Recently, biological evidences have indicated that PTGS and transcriptional gene silencing (TGS), induced by endogenic small RNAs (sRNAs), are evolving as significantly crucial drivers of ETI and PTI signaling pathways, as well as R gene expression (Zhai et al 2011;Baltusnikas et al 2018;Tan et al 2020;Sanan-Mishra et al 2021). Furthermore, several classes of microorganisms, such as plant viruses, bacteria, and oomycetes, have been discovered to produce suppressor proteins as part of their virulence effectors, to suppress RNA silencing in host plants and cause disease (Navarro et al 2008;He et al 2019).…”
Section: Antiviral Rna Silencing and Plant Immunitymentioning
confidence: 99%
“…The mechanism of antiviral RNA silencing in plants reveals a related process, termed as post-transcriptional gene silencing (PTGS). Recently, biological evidences have indicated that PTGS and transcriptional gene silencing (TGS), induced by endogenic small RNAs (sRNAs), are evolving as significantly crucial drivers of ETI and PTI signaling pathways, as well as R gene expression (Zhai et al 2011;Baltusnikas et al 2018;Tan et al 2020;Sanan-Mishra et al 2021). Furthermore, several classes of microorganisms, such as plant viruses, bacteria, and oomycetes, have been discovered to produce suppressor proteins as part of their virulence effectors, to suppress RNA silencing in host plants and cause disease (Navarro et al 2008;He et al 2019).…”
Section: Antiviral Rna Silencing and Plant Immunitymentioning
confidence: 99%
“…The lncRNAs can also guide gene silencing through siRNA-dependent DNA methylation [47]. The role of small RNA-directed DNA methylation (RdDM) and heterochromatinization has been well studied in plants [138][139][140]. The plant-specific RNA polymerases, RNA Pol IV and V play a crucial role in this process [24,51,[141][142][143][144].…”
Section: Lncrnas In Dna Modificationmentioning
confidence: 99%
“…Briefly, Pol IV, along with the CLASSY chromatin remodeling factors (CCRFs) and homeodomain transcription factors, such as DTF1/ SHH1, transcribes transposons and repetitive sequences. The transcripts are converted to double-stranded RNAs (dsRNAs) by the action of RNA-dependent RNA polymerase-2 (RDR2) and the dsRNAs are processed into small ncRNAs, specifically siRNA duplexes by Dicer-like 3 (DCL3) enzyme [138,139]. These siRNAs are loaded in Argonaute 4 (AGO4)-containing complex to guide RdDM.…”
Section: Lncrnas In Dna Modificationmentioning
confidence: 99%
See 2 more Smart Citations